MODELING OF BUSINESS PROCESSES ON THE BASIS OF BUILDING AN OPTIMAL SYSTEM OF COMPLEXING ADAPTIVE-ORGANIZATIONAL MECHANISM MANAGEMENT OF ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article is devoted to topical issues of research of peculiarities of business process modeling on the basis of construction of optimal system of complexing of adaptive-organizational mechanism of management. The study developed a scientific approach to business process modeling based on the use of complex adaptive-organizational management mechanism through simulation modeling of business processes based on matrix construction, which gives a more accurate assessment of the system and more fully describes the cause-and-effect relationship –«status-adaptation-management-status» оn the enterprise. The researched description of the given functional dependences with use of a method of simulation modeling of business processes gives the chance to construct dynamics of forecast states of system of activity of the enterprise that will avoid erroneous decisions and will allow to construct subspace of management business-processes of the enterprise.
Keywords: management, enterprise, modeling, business processes, management mechanism, system of complexing adaptive-organizational management mechanism.